Factors affecting nutritional status in toddlers in Sumberejo Village Batu District Batu City - Susana Setyowati; Sayuti Sayuti; Qotimah Qotimah (Journal of Midwifery and Nursing, 2023)
Nutritional status is a toddler's health condition which is assessed from physical form including height/weight. Indicators of nutritional status in children under five aged 2-5 years use Body Weight (BB) / Height (TB). The nutritional status of children under five is very important to know because it is an indicator of the quality of human resources that determines the level of community welfare. Toddlers who have good nutritional status are an important element in fulfilling nutritional needs, considering that nutrients function to produce energy, build and maintain tissue, regulate life processes in the body and meet the needs for growth and development of toddlers. The purpose of this study was to determine the factors that influence nutritional status in toddlers in Sumberejo Village, Batu District, Batu City. This study used an analytic survey research method with a case control approach, namely an analytic survey (research) involving how risk factors were studied using a retrospective approach. The sample in this study were mothers who had toddlers in Sumberejo Village, Batu District, Batu City, totaling 34 mothers. The results of data analysis show that family income (X2) The calculated X2 value is 20,864 <X2 table (3.84), knowledge (X3) The calculated X2 value is 20,864 <X2 table (3.84), history of infectious diseases (X5) The calculated X2 value is 20,864 < X2 table (3.84), Exclusive Breastfeeding (X6) X2 calculated value is 20,864 < X2 table (3.84), Nutrition Intake (X7) X2 calculated value is 20,864 < X2 table (3.84) with Asymp value. Sig. (2-sided) 0.000 <0.05 means that H0 is rejected and H6 is accepted, so it can be concluded that there is a significant effect on the nutritional status of toddlers (Y). While the education factor (X1) the X2 count value of mother's education is 2.391 < X2 table (3.84), parenting style (X4) The X2 count value is 2.391 < X2 table (3.84) with Asymp value. Sig. (2-sided) 0.122 > 0.05 means that there is no significant effect on the nutritional status of toddlers (Y).